AB1204 COST-EFFECTIVENESS OF ABATACEPT IN SPAIN IN SEROPOSITIVE BIOLOGIC-NAÏVE EARLY RHEUMATOID ARTHRITIS PATIENTS WITH SHARED EPITOPE. (2nd June 2020) - Rodríguez-Heredia, J. M.; Verburg-Baltussen, L.; Devender, D.; Durno, N.; Sanchez, C.; Ray, N.; Treur, M.; Zhuo, J.
Abstract : Background: The HLA class II Shared Epitope (SE) is a known Rheumatoid Arthritis (RA) risk allele linked to autoantibody production and disease progression. The recent Early AMPLE study suggests an enhanced treatment benefit of abatacept (ABA) over adalimumab (ADA) in SE positive patients with early seropositive RA. 1 Economic implications beyond the trial follow-up duration are unknown. Objectives: To estimate the cost-effectiveness of ABA vs ADA in biologic-naive RA patients seropositive for anti-citrullinated protein antibody and rheumatoid factor based on the Early AMPLE study. Methods: We developed a microsimulation model to estimate clinical response, medical cost, quality of life and survival from a Spanish payer perspective. The model captures the patient's disease and treatment journey using response outcomes and the Health Assessment Questionnaire (HAQ) score. Patients who fail to respond switch to the next treatment line. Six treatment lines are included to capture a lifetime horizon. Responding patients (ACR50 and EULAR response) achieve an improvement in their HAQ score. Patient mortality was modelled as a function of HAQ. For both the overall Early AMPLE population and SE+ patients, incremental monthly cost per response over 2 years and incremental cost per QALY over a lifetime were estimated. Costs were based on local tariffs in Spain. Results: Baseline characteristics for the Early AMPLE (n=80) and the SE+ (n=61) patients were well balanced between the treatment groups. 2 Compared to ADA, the ABA cohort had a lower cost per response and the difference was more pronounced in the SE+ population, compared to the entire Early AMPLE population for both the response criteria (Table 1 ). Compared with ADA, the ABA cohort showed greater quality adjusted life years (QALYs) gains, and a modest increase in cost due to a prolonged time on treatment (Table 2 ). The incremental cost per QALY over a lifetime fell below commonly used thresholds in Spain (25-60 thousand Euros per QALY). 3 Conclusion: Compared with ADA, ABA is a cost-effective alternative and is associated with a lower 2 years cost per response for both populations. The economic benefit and quality of life gain is greater in a SE+ patient population. References: [1]Rigby W, et al. EULAR Annual Meeting, June 2019; Poster LB0008 [2]Buckner J, et al. ACR/ARP Annual Meeting, Nov 2019; Poster 1424 [3]Sacristán JA, et al. Gaceta Sanitaria 2019 Disclosure of Interests: José M. Rodríguez-Heredia: None declared, Lisanne Verburg-Baltussen Consultant of: Consultant for Bristol-Myers Squibb, Paid instructor for: Training sessions for Pharmaceutical companies, Dhanda Devender Shareholder of: BMS, Employee of: BMS, Nicholas Durno Consultant of: Consultant for Bristol-Myers Squibb, Paid instructor for: Training sessions for Pharmaceutical companies, Carlos Sanchez Shareholder of: Shareholder of Bristol-Myers Squibb, Employee of: Bristol Myers-Squibb, Neelanjana Ray Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Maarten Treur Consultant of: Consultant for Bristol-Myers Squibb, Paid instructor for: Training sessions for Pharmaceutical companies, Joe Zhuo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb